Critically Examining The Arrangements of Fiscal Decentralization in Indonesia - Bachtiar, Rizqi (Faculty of Social and Political Science Universitas Brawijaya, 2018)
As an implication of the implementation of decentralization in Indonesia, the authority to manage income and spending autonomously by local governments in Indonesia is undeniable. However, the power should be managed and used proportionally. The central government should not lose its control of the local governments, while the local governments maintain the authority to manage its area. This paper examines the proportions of the fiscal authority given by the central government to the local governments in Indonesia. In short, this research finds that in general, the framework of fiscal decentralization in Indonesia is going well. Some research also offers positive findings of fiscal decentralization in Indonesia. However, there are also some serious problems resulting from the implementation of fiscal decentralization in Indonesia, such as vertical fiscal imbalance and corruption. These problems need to be reduced by issuing technical and specific regulations and by ensuring that those regulations are both monitored and implemented.